2021
DOI: 10.3390/ijerph18115677
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapy-Induced Peripheral Neuropathy on Quality of Life in Patients with Advanced Lung Cancer Receiving Platinum-Based Chemotherapy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common adverse effect of neurotoxic anticancer drugs that may affect quality of life (QoL). Purpose: The purposes of this study were to: assess the levels of CIPN, anxiety, depression, CIPN–related QoL, and general QoL; and identify the factors related to CIPN–related QoL and general QoL in patients with advanced lung cancer (LC) receiving platinum-based chemotherapy. This cross-sectional study examined patients with advanced LC who received platinum-based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…This study was conducted to analyze data from gynecological cancer patients undergoing chemotherapy to understand the relationship between peripheral neuropathy symptoms, self-care ability, and disturbances to daily life, and identify the factors that affect QoL. The QoL of gynecological cancer patients in this study was lower than in prior international and domestic studies conducted using the same instrument, which included QoL scores of 64.8 points [11], 78.8 points [28], 67.69 points [29], and 69.32 points [30]. The low QoL in this study was likely due to the high proportion of ovarian cancer patients at 70%; over 60% to 70% of whom had stage 3 or 4 cancer when they were diagnosed, as over 70% may experience recurrence even after treatment [15].…”
Section: Discussionmentioning
confidence: 80%
“…This study was conducted to analyze data from gynecological cancer patients undergoing chemotherapy to understand the relationship between peripheral neuropathy symptoms, self-care ability, and disturbances to daily life, and identify the factors that affect QoL. The QoL of gynecological cancer patients in this study was lower than in prior international and domestic studies conducted using the same instrument, which included QoL scores of 64.8 points [11], 78.8 points [28], 67.69 points [29], and 69.32 points [30]. The low QoL in this study was likely due to the high proportion of ovarian cancer patients at 70%; over 60% to 70% of whom had stage 3 or 4 cancer when they were diagnosed, as over 70% may experience recurrence even after treatment [15].…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, people with advanced cancer often have continuous chemotherapy cycles where acute or chronic CIPN is experienced, which presents a unique challenge for this population. Symptoms of CIPN can negatively affect sleep, mood, mobility, activities of daily living, and lead to distress, anxiety, depression, financial toxicity, difficulty feeding, constipation and diarrhea, which further compromise cancer treatment outcomes and quality of life [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The taxane, platinum, and vinca alkaloids are the agents most commonly associated with CIPN. It can cause dysfunction of motor, sensory and autonomic neurons, manifesting as signs and symptoms of peripheral neuropathic, including sensory damage[ 1 ]. The mechanisms of peripheral neuropathy induced by oxaliplatin and taxane drugs are ion channels altering the excitability of peripheral neurons, mitochondrial damage leading to peripheral nerve apoptosis, and inflammation leading to nociceptor sensitization and the development of neuroinflammation[ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the treatment, there is an improvement over time, but some patients continue to have symptoms for many years[ 4 ]. Among patients with advanced lung cancer treated with oxaliplatin regimens, 53.8% reported sensorineural impairment, and 47.3% reported motor neuron impairment[ 1 ]. Selvy et al [ 9 ] showed that 36.5% of patients still had CIPN 5 years after the end of oxaliplatin chemotherapy.…”
Section: Introductionmentioning
confidence: 99%